Repetitive Transcranial Magnetic Stimulation for Tinnitus Treatment in Vestibular Schwannoma: A Pilot Study - Leao, Maria Teresa; Machetanz, Kathrin; Sandritter, Joey; Liebsch, Marina; Stengel, Andreas; Tatagiba, Marcos; Naros, Georgios (Frontiers in Neurology, 2021)
Background: Vestibular schwannomas (VS) are brain tumors affecting the vestibulocochlear nerve. Thus, VS patients suffer from tinnitus (TN). While the pathophysiology is mainly unclear, there is an increasing interest in repetitive transcranial magnetic stimulation (rTMS) for TN treatment. However, the results have been divergent. In addition to the methodological aspects, the heterogeneity of the patients might affect the outcome. Yet, there is no study evaluating rTMS exclusively in VS-associated tinnitus. Thus, the present pilot study evaluates low-frequency rTMS to the right dorsolateral pre-frontal cortex (DLPFC) in a VS-associated tinnitus. Methods: This prospective pilot study enrolled nine patients with a monoaural VS-associated tinnitus ipsilateral to the tumor. Patients were treated with a 10-day rTMS regime (1 Hz, 100% RMT, 1,200 pulses, right DLPFC). The primary endpoint of the study was the reduction of TN distress (according to the Tinnitus Handicap Inventory, THI). The secondary endpoint was a reduction of TN intensity (according to the Tinnitus Matching Test, TMT) and the evaluation of factors predicting tinnitus outcome (i.e., hearing impairment, TN duration, type of tinnitus). Results: No complications or side effects occurred. There was one drop-out due to a non-responsiveness of the complaint. There was a significant acute effect of rTMS on the THI and TMT. However, there was no significant long-term effect after 4 weeks. While the THI failed to detect any clinically relevant acute effect of rTMS in 56% of the patients, TMT revealed a reduction of TN intensity for more than 20 in 89% and for more than 50 in 56% of the patients. Notably, the acute effect of rTMS was influenced by the TN type and duration. In general, patients with a tonal TN and shorter TN duration showed a better response to the rTMS therapy. Conclusion: The present pilot study is the first one to exclusively evaluate the effect of low-frequency rTMS to the right DLPFC in a VS-associated tinnitus. Our results prove the feasibility and the efficacy of rTMS in this patient cohort. There is a significant acute but a limited long-term effect. In addition, there is evidence that patients with a tonal tinnitus and shorter tinnitus duration might have the strongest benefit. A larger, randomized controlled study is necessary to prove these initial findings.